Eudaimonia and the political and ethical spheres in Aristotle: is it possible to think the human good regardless of a political field? (2016)
This article tries to show the potential relationship between the political sphere and ethical sphere in Aristotle’s thought. Are the political and the ethical research projects distinguishable or, in contrasts, are one research project? To answer this question, I suggest that, in the first place, it is necessary to answer the question about the nature of final good. Then, I analyze a property of eudaimonia, namely, autarchy. This analysis will show how, depending on the answer given to the second question, the first can be answered.